Growth trajectories of the established companies : effectuation and causation in focus - Matalamäki, Marko (Vaasan yliopisto, 2018)
Business growth is one of the key topics of today’s entrepreneurship research. The majority of the publications related to the growth entrepreneurship focus on exploring growth among new companies, and the public economic debate targets high expectations for growth entrepreneurship by new companies and startups. Established companies are generating growth, but their potential seems marginalized in an economical discussion. It is important to consider both new and established companies when expecting new growth from companies. The main objective of this research is to enhance our understanding of the determinants that cause a growth surge among established companies after some years of consolidation. Are these companies adapting to the situation and responding to the demands of the market with their resources (effectuation), or do they follow previously determined plans and proceed toward set goals (causation). The findings indicate the usage of both effectuation and causation logics, between which effectuation appears the dominant approach. This dissertation contributes by building a model showing that causation and Chandler’s (2011) dimensions of effectuation do have an impact on firm-level innovativeness and ultimately business growth. The developed model shows that interaction between flexibility and growth is positive and significant. This study strengthens the recent findings that effectuation and causation can work simultaneously in the same company. Moreover, the results show that effectuation research has moved on from the nascent to an intermediate stage of development, and has already taken the first steps toward the mature stage, where a growing number of scholars are currently engaging in quantitative field research to study the phenomenon in its real environment.

Kasvuyrittäjyys on noussut viime vuosina yrittäjyystutkimuksen yhdeksi tärkeimmäksi osa-alueeksi. Valtaosa kasvuyrittäjyyteen liittyvistä julkaisuista keskittyy uusien ja aloittavien yritysten kasvun tutkimiseen, myös julkinen keskustelu lataa kovia kasvuodotuksia nimenomaan uusille yrityksille ja startupeille. Vakiintuneet yrityksetkin tuottavat kasvua, mutta niiden potentiaali pääsee usein unohtumaan talouskeskustelussa. Tämän tutkimuksen päätavoite on lisätä ymmärrystä tekijöistä, joiden seurauksena vakiintuneet yritykset lähtevät kasvu-uralle tasaisen kehitysvaiheen jälkeen. Tarkennettuna, tapahtuuko kasvupyrähdys toimimalla tilanteen ja kysynnän mukaisesti ja vastaamalla markkinoiden vaatimuksiin olemassa olevilla resursseilla, vai onko kasvu pikemminkin seurausta tehtyjen strategisten suunnitelmien noudattamisesta. Tulokset osoittavat sekä tilanteen mukaisen toiminnan logiikan toteuttamisen että strategian noudattamisen vaikuttavan näiden yritysten kasvuun. Hallitsevana logiikkana tutkituissa pk-yrityksissä näyttäisi esiintyvän tilanteen mukainen toiminta. Tämän väitöskirjan osuus tieteelliseen keskusteluun on rakennettu malli, joka osoittaa, että strategian noudattaminen ja joustavuus vaikuttavat yrityksen innovaatiotoimintaan ja sen myötä liiketoiminnan kasvuun. Toinen kehitetty malli osoittaa, että joustavuuden ja yrityskasvun välinen vuorovaikutus on myönteinen ja merkittävä. Tämä tutkimus vahvistaa viimeaikaisia havaintoja siitä, että tilanteen mukainen toiminta ja suunnitelmallisuus voivat toimia samanaikaisesti samassa yrityksessä. Lisäksi tulokset osoittavat, että tilanteen mukaisen toiminnan (effectuation) tutkimus on tutkimussuuntauksena siirtynyt alkukehitysvaiheesta välivaiheeseen ja ottanut jo ensimmäiset askeleet kohti kypsää tutkimusvaihetta, jossa tutkimukselle ominaisia tunnustekijöitä ovat kvantitatiiviset tutkitusmenetelmät ja ilmiön tutkiminen todellisessa tapahtumaympäristössä.
Keywords: effectuation; causation; business growth; growth orientation; yrittäjyys; kasvu; innovaatiotoiminta; fi=Johtaminen ja organisaatiot|en=Management and Organization|